2010
DOI: 10.1177/1359105309345554
|View full text |Cite
|
Sign up to set email alerts
|

Pain, Coping and Health Care Utilization in Younger and Older Adults with Sickle Cell Disease

Abstract: Sickle cell disease is characterized by acute pain crises. Pain, chronic medical problems, utilization and coping were compared in younger vs older patients using questionnaires and medical record review. Groups reported similar pain intensity and medical conditions. The pattern of utilization differed such that older patients attended outpatient clinic, and younger patients went to the Emergency Department. Younger patients were more likely to cope by ignoring pain, or by using heat, cold or massage. Older pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 26 publications
(35 reference statements)
2
30
0
Order By: Relevance
“…The tradition of consanguineous marriage in Middle Eastern countries, which varies between 25% in Lebanon to 60% in Saudi Arabia and 90% in some Bedouin communities in Kuwait and Saudi Arabia, is a major contributor to the multiplication of SCD (El-Hazmi et al, 2011). Although it is inherited genetically, the symptoms and course of the disease (HbS) can be affected by environmental factors such as infections, nutrition, and socioeconomic status (Sanders, Labott, Molokie, Shelby, & Desimone, 2010). Among the hemoglobinopathies, SCD and b-thalassemia are the most common and have the highest impact on morbidity and mortality, with more than 330,000 infants diagnosed annually.…”
mentioning
confidence: 99%
“…The tradition of consanguineous marriage in Middle Eastern countries, which varies between 25% in Lebanon to 60% in Saudi Arabia and 90% in some Bedouin communities in Kuwait and Saudi Arabia, is a major contributor to the multiplication of SCD (El-Hazmi et al, 2011). Although it is inherited genetically, the symptoms and course of the disease (HbS) can be affected by environmental factors such as infections, nutrition, and socioeconomic status (Sanders, Labott, Molokie, Shelby, & Desimone, 2010). Among the hemoglobinopathies, SCD and b-thalassemia are the most common and have the highest impact on morbidity and mortality, with more than 330,000 infants diagnosed annually.…”
mentioning
confidence: 99%
“…After removing duplicated articles, 14 articles were deemed eligible entering the review process ( Figure 1). However, just five studies had examined the effect of massage on reducing pain in patients with sickle cell experimentally (31)(32)(33)(34)(35); the other 9 studies had just evaluated the rate of use of massage as a complementary medicine by patients (4,30,(36)(37)(38)(39)(40)(41)(42).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Sanders et al (2010) showed that younger people use massage therapy more significantly (P = 0.02) to relieve their pain (39).…”
Section: Discussionmentioning
confidence: 99%
“…Predictably, the substantial pain associated with the condition has been of particular interest to researchers. An example is the Sanders, Labott, Molokie, Shelby, and Desimone (2010) study that examined the differences between two age groups of those with sickle cell (8-36 years and 37-62 years) in the USA in relation to pain management and use of healthcare facilities.…”
Section: The Management Of Scdmentioning
confidence: 99%
“…In terms of utilising the healthcare system, the young people in the study preferred hospital admission and the emergency department, while older people were more likely to access an outpatient department option. Sanders et al (2010) highlighted age as a significant factor influencing coping strategies and decisions on preferred access to healthcare. As stated by Caird et al (2011), patients with sickle cell disease develop a differing relationships with their illness as their life circumstances and experiences change.…”
Section: The Management Of Scdmentioning
confidence: 99%